Hospital admissions for gastroenteritis in a Western Amazon capital: an epidemiological overview (Research, Society and Development, 2022)
The hospital admissions due to gastroenteritis are characterized by preventable, sensitive and treatable conditions in Primary Health Care. To analyze the prevalence of hospital admissions due to gastroenteritis in the capital of the Western Amazon. This is a descriptive epidemiological study, carried out in a cross-sectional and quantitative approach in the city of Porto Velho, Rondônia, based on the survey of the variables (age, sex, race/color, health establishment, character of care, year number of care and average length of stay) of children under 4 years of age at the SUS Department of Informatics (DATASUS), from 2010 to 2020. Subsequently, descriptive statistical analysis of the results was performed using the Microsoft Excel program. There were 2,045 records of hospitalizations for gastroenteritis in Porto Velho, of which the majority were between 1 and 4 years old (67.3%) and, regardless of age group, they were male (54.9%), race/brown color (83, 5%), with care provided at the Children's Hospital (92.9%) on an urgent basis (99.8%), with a decrease in care and an increase in the average length of stay. In view of these findings, it is essential to reflect on the planning, development and effectiveness of preventive measures and sustainable intervention measures for the control of gastroenteritis.